The effects of sewing thread properties and stitch densities on seam strength at different seam angles [Dikiş iplik özelliklerini ve dikiş sikliklarinin farkli dikiş açilarinda dikiş mukavemeti üzerine etkileri] - (:unkn) unknown (My University, 2011)
In this paper, it was aimed to determine the effects of various sewing thread and stitch densities on the seam strength and seam extension in different sewing angles. In order to provide this, 100% wool fabric and three different types of sewing thread have been used as material. Fabrics have been cut in the angle of 0o, 30o, 45o, 60o, 90o, and then sewn respectively in the density of 4 stitch/cm and 5 stitch /cm, with lockstitch and chain stitch for the each angle type. These prepared samples evaluated in terms of seam strength and seam extention. The empirical results were analyzed by using the SPSS statistical software programme. As a result of this study, it was not seen a significant differences in the fabric's strength and extension interms of the sewing type. It was observed that, the fabric which is sewn in 45o bias angle, have much more strength from the others. It was determined that the most flexible fabric was sewn in 450 bias angle and the second one was the 600 bias angle. The fabric with the stitch densty of 5 stitch/cm has more strength and extension than the other stitch density. It was conceived that, there was no difference in the fabric strength and extension in terms of the type of yarn used in sewing.
Keywords: Seam angle; Seam extension; Seam strength; Sewing thread; Stitch density